Redes sociales digitales en la migración trasnacional romá de Rumanía. Una "polymedia" transnacional - Ogáyar-Marín, Francisco-Javier; Muntean, Vasile; Gamella-Mora, Juan-Francisco (Revista de Humanidades, 2018)
Resumen: En este artículo estudiamos la convergencia de la migración romá rumana posterior a 1989 con el desarrollo de las tecnologías de la información y la comunicación (TIC) a partir de ese mismo período. Para ello hemos partido del trabajo etnográfico previo realizado durante dos campañas entre 2003-2007 y 2013-2016 respectivamente con siete redes romá Korturare procedentes de las regiones rumanas de Transilvania y el Bánato, centrándonos en tres de ellas por su presencia en la ciudad de Granada. El rol de los recursos de polymedia, un entorno emergente de posibilidades comunicativas, facilita y alienta los desplazamientos migratorios al reducir incertidumbres y permitir experiencias de copresencia (digitalizada) en un contexto transnacional. Esta situación favorece dinámicas de reproducción y control cultural, pero a la vez habilita y permite usos diferenciados en polymedia que esbozan transformaciones en las costumbres romá. Abstract: In this paper we explore the convergence of two contemporary parallel processes: the post-1990 transnational migration of Roma groups from some Eastern European countries, particularly Romania to the West, and the growing use by these populations of the expanding social media derived from the revolutionary development of new ICT (information and communication technologies). We have followed some groups from Transylvania and Banat to their western diaspora in a long-term ethnographic work that started in 2003 and was retaken in a recent ethnographic project (2013-2017). We have studied primarily groups living in Andalusia, although their family networks are extended today over more than 30 localities in a dozen of European and North American countries. These networks of networks form a social space or commuinity or reference that is largely maintained through digital communication. The different social media and communication options (from Facebook to cheap phone calls) generate a new kind of virtual environment or polymedia (Madianou and Miller 2011, 2012). In this paper we explore the effects of this new social space of communication in three major aspects of Roma social life: 1)Its effects in facilitating, supporting and inducing mobility and migration; 2) In cultural reproduction and transformation through the maintenance of specific systems of family, marriage, gender and conflict resolution, including the online transmission of public trials and courts (kris), funerary rituals and elaborated marriage ceremonies, including betrothal (mangaimo) and weddings (abev); and 3)In new processes of social distinction and differentiation following fracture lines of class, gender and generation.